2014
DOI: 10.22546/27/531
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de un modelo de asistencia clínica compartida con internistas en un servicio de cirugía vascular

Abstract: ORIGINALAnálisis de un modelo de asistencia clínica compartida con internistas en un servicio de cirugía vascular Analysis of a comanagement clinical model with internists in a vascular surgery department ResumenObjetivo: valorar si la asistencia clínica compartida entre cirujanos vasculares e internistas mejora la calidad de la atención médica prestada a pacientes ingresados en un servicio de cirugía vascular.Material y método: se analizaron diversas características clínicas relativas a la atención de una mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Even if the results are only indirectly comparable, Vidán et al demonstrated that early multidisciplinary daily geriatric care led to a reduction in in-hospital mortality and medical complications in elderly patients with hip fracture [ 24 ]. And a Spanish study from 2014 aimed to answer the question whether the co-management with Internal Medicine physicians would improve the care of vascular surgery patients [ 25 ]. Compared to controls of the year before, study patients showed a higher frequency of identified thrombosis risk factors, an improved use of the correct heparin dose adapted to weight and kidney function, as well as higher percentage of identified comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if the results are only indirectly comparable, Vidán et al demonstrated that early multidisciplinary daily geriatric care led to a reduction in in-hospital mortality and medical complications in elderly patients with hip fracture [ 24 ]. And a Spanish study from 2014 aimed to answer the question whether the co-management with Internal Medicine physicians would improve the care of vascular surgery patients [ 25 ]. Compared to controls of the year before, study patients showed a higher frequency of identified thrombosis risk factors, an improved use of the correct heparin dose adapted to weight and kidney function, as well as higher percentage of identified comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…No difference was seen regarding the length of the hospital stay. Based on a survey, physicians as well as nursing staff preferred the co-management model over the standard model [ 25 ]. However, direct comparison to this study is difficult as in the Spanish study internists where available on a regular daily basis in the emergency department as well as for daily follow-ups, compared to once-weekly rounds.…”
Section: Discussionmentioning
confidence: 99%